Influence of BIM-Based Teaching Methodology on the Spatial Abilities of Construction Engineering Students - Pulido-Arcas, Jesús Alberto; Martínez-Rocamora, Alejandro; Folgar-Erades, Alejandro (Advances in Building Education, 2021)
Spatial visualization skills are considered essential for a variety of professional careers, especially those related with architecture, engineering, and construction (AEC). A number of studies have proven that these skills are progressively acquired by AEC students during their years in college, being necessary specific pedagogical approaches for this purpose. Other 3D native design software has been proved to exert a positive influence on the spatial abilities of students in several fields, such as fine arts or civil engineering. In the field of AEC, BIM software stands out as an appropriate tool for this purpose, as it supports 3D-native design. This study was conducted to clarify the influence that working with BIM models has on the spatial abilities of the students to visualize constructive components in 3D; it was hypothesized that the effect would be positive to some extent, as in similar disciplines. To that end, an experiment was conducted with 73 undergraduate students in construction engineering, who attended an intensive 4-week workshop where they had to work with BIM models. The improvement in their spatial abilities was measured by the Mental Rotation Test (MRT) and, besides, a satisfaction survey was conducted. The results indicate that MRT scores improved between 3.8% and 15.5% and that students felt highly satisfied with this pedagogical approach. These results aim to help in implementing BIM in the academic curricula to maximize the educational outcomes of the students while gathering their assessment of BIM-based teaching methodologies.